Mystery: Poetizing by Way of Gelassenheit Toward a Pedagogy of Awe - Harvey, Sharon R.; Karrow, Douglas D. (Journal of the Canadian Association for Curriculum Studies, 2025)
Common ways of thinking in education revolve around the purposes of science, curiosity and calculative modes of thought, resulting in instrumental methods and ends in education and teacher education. Mystery, defined as physis from ancient Greek metaphysics, which highlights both presence and absence, is typically left out of knowing, teaching and learning. Today’s education can benefit from unique approaches emphasizing mystery as presence and absence through “poetizing” or poetic engagement. Poetic knowledge, meditative thinking and awe provide new ways of experiencing curriculum and pedagogy. Borrowing from Martin Heidegger’s Gelassenheit, or “letting be”, and poetizing after this manner, provides a particular posture for encountering things differently in non-objectified ways. Curiosity and awe in curriculum, emotional responses related to mystery, give insight for showcasing the importance of non-objectification, a re-situated stance toward things in an increasingly technological era. For mystery to take its place in education, it will require a move from calculative thinking to meditative thinking, from curiosity to awe, by way of poetizing (qua Gelassenheit).